Aerobic Palladium(II) catalysed oxidative route for synthesis of Papaveraldine (Indian Journal of Chemistry (IJC), 2026)
In this paper, an alternate chromatography free route employing aerobic Palladium(II) catalysed base mediated oxidative conditions for synthesis of medicinally promising alkaloid Papaveraldine is reported.